COMPETITIVE DAN CONTAGION EFFECTS DALAM TRANSFER INFORMASI INTRA INDUSTRI TERHADAP PENGUMUMAN STOCK SPLIT - Shinta Heru Satoto; Hasa Nurrohim KP (University of Merdeka Malang, 2008)
The purpose of this research was to investigate the intra industry informationtransfers on stock split announcement at manufactured industries. This research would alsoinvestigate the contagion and competitive effect of the announcement and the factors thatinfluenced this effect. Result of this research showed that there was an abnormal return onsplitting and nonsplitting firms, and the competitive effects that influenced this research(industry characteristic, firms specific characteristics, earning correlation and return variance).However, those factors could not explain the information transfers. This reaction did notinfluence the earning changes of nonsplitting firms